RANCANG BANGUN SISTEM REKAYASA SUHU PADA LARUTAN IODINE CLOCK - Robbith Qosath Al Auhi; Adharul Muttaqin; Panca Mudjirahardjo (Jurnal Mahasiswa TEUB, 2022)
The iodine clock reaction is when two clear solutions are mixed, producing another clear solution. After a while, the solution will instantly turn dark blue. The time for iodine clock reaction to change color can be used as a timer for the stoping mechanism on a chemically powered car prototype in Chem E Car competition. This temperature conditioning system aims to reduce the error of the iodine clock reaction time by adjusting the temperature to remain constant before being injected. In this study, the DS18B20 sensor was used to measure the solution temperature and DHT11 sensor to measure the ambient temperature. The OLED display used to showing sensor reading data. This system is designed to control the temperature of the solution to reamin constant with a setpoint range from ambient temperature to 50°C using PID control with Cohen-Coon tuning method. Parameter value obtained from this Cohen-Coon tuning method are Kp=10,25119, Ki=0,01754, Kd=780,66828. The actuator uses in this system are PTC heating element as a heater and DC fan as a cooler. The DS18B20 sensor readings and the control process are processed by Arduino Uno while the DHT11 readings and monitoring system are processed by